Clinical features and prognostic factors of pediatric Langerhans cell histiocytosis: a single-center retrospective study - Yunfeng Lu; Liying Liu; Qi Wang; Bingju Liu; Ping Zhao; Guotao Guan; Yunpeng Dai (Frontiers in Medicine)
PurposeTo retrospectively evaluate the clinical features and prognostic factors of pediatric LCH patients treated in a single center of China.MethodsPediatric LCH cases were treated following the SD-LCH protocol at the Affiliated Provincial Hospital of Shandong First Medical University in Jinan, China. An analysis was conducted on 82 recently identified LCH cases to retrospectively evaluate the initial symptoms, therapeutic alternatives, and extended results. Follow-ups were conducted until July 31, 2023.ResultsThe median age at diagnosis was 2 (0.25–12) years. 42 (51.2%) were SS-LCH, and 40 (48.8%) were MS-LCH. The most common organ involved was bone (82.9%). Over the 16-year follow-up period, the 5-year EFS and OS rates were 75.2 ± 5% and 90.9 ± 3.3%, respectively. The cumulative reactivation rate was 23.2%. The 5-year EFS rate in SS-LCH and MS-LCH patients were 90.2 ± 4.6% and 58.8 ± 8.3%, and the 5-year OS rate in SS-LCH and MS-LCH patients were 90.2 ± 4.6% and 81.2 ± 6.5%, respectively. The 5-year OS and EFS rate in RO+ LCH and RO− LCH patients were 79.5 ± 7.5%, 53.8 ± 9.6% and 87.5 ± 11.7%, 76.2 ± 14.8%, insignificantly. Multivariate Cox regression showed that liver involvement predicted poor EFS and hematological system involvement was an independent prognostic factor for OS. Detection of the BRAFV600E mutation and targeted therapy significantly improved the prognosis post-2017.ConclusionLiver or hematological system involvement indicates a poor prognosis, and the SD-LCH protocol improves prognosis for pediatric LCH patients.